Chapter 12 Children's perspectives on green space management in Sweden and Denmark - Jansson, Märit (Taylor & Francis, 2020)
Green space managers develop and maintain urban green spaces, where children are often among the most frequent users. In a case study of four urban districts in Sweden and Denmark, focusing on children aged 10-11, the authors collected children's texts and drawings and conducted child-led walks with group conversations about places, activities, preferences and suggestions. Children's use of their local outdoor environments and their views on green space management varied, but they seldom perceived management as something they could affect. We recommend children's experiences and opinions as a rich resource for green space managers and an important aspect of child friendliness.